Analysis Of The Influence Of Fundamental Variables on Stock Investment Decisions In Energy Sector Companies on The IDX For The 2019–2023 Period - Wahyu Aji Pradana; Ulil Hartono (Universitas Negeri Surabaya, 2026)
The Indonesian capital market has experienced rapid growth with an increasing number of Investors, especially in the energy sector, which plays an important role in the national economy. This dynamic requires Investors to consider fundamental factors in determining investment decisions. This study aims to analyze the influence of Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), Earnings per Share (EPS), Price to Book Value (PBV), inflation, and interest rates on stock investment decisions proxied by the Price Earnings Ratio (PER), in energy sector on the Indonesia Stock Exchange for the 2019–2023 period. This study used 270 observations with 54 companies selected using purposive sampling techniques, then analyzed using panel data regression on STATA 17 software. The results of the study show that all variables simultaneously influence investment decisions. Partially, ROA, ROE, and DER have a positive effect, EPS has a negative effect, while PBV, inflation, and interest rates have no effect on investment decisions. The R² value of 46.20% indicates that almost half of the variation in investment decisions can be explained by the model. Therefore, Investors are advised to prioritize profitability factors and capital structure in assessing the prospects of energy sector stocks, while companies need to maintain asset efficiency, improve equity performance, and manage debt structure carefully in order to strengthen Investor confidence and increase investment attractiveness.